2019
DOI: 10.1111/ap.12363
|View full text |Cite
|
Sign up to set email alerts
|

Functioning with fibromyalgia: The role of psychological flexibility and general psychological acceptance

Abstract: Objectives Fibromyalgia is a chronic condition characterised by widespread musculoskeletal pain, fatigue, mood disturbances, and cognitive difficulties. Psychological flexibility (PF), particularly acceptance of pain, has been associated with the physical and psychological functioning (functional status) of chronic pain patients. Further investigation is required to assess the unique contribution of PF model components to functional status in people with fibromyalgia. This study investigated the role of both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
(114 reference statements)
2
5
0
Order By: Relevance
“…Taking into account the most dysfunctional profile represented by Group 1, the low pain acceptance seems to be a relevant variable linked to severity of FM, which is in line with previous research (e.g., Lami et al, 2018;Tangen et al, 2020;Trainor et al, 2019). However, beyond the low pain acceptance, other processes of psychological inflexibility may be involved in FM experience.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Taking into account the most dysfunctional profile represented by Group 1, the low pain acceptance seems to be a relevant variable linked to severity of FM, which is in line with previous research (e.g., Lami et al, 2018;Tangen et al, 2020;Trainor et al, 2019). However, beyond the low pain acceptance, other processes of psychological inflexibility may be involved in FM experience.…”
Section: Discussionsupporting
confidence: 87%
“…Pain acceptance is defined as the willingness to live with pain with no need to try to change it (Thompson & McCracken, 2011) and evidence suggests that contributes in a powerful way to developing a more constructive pain experience. In FM patients several studies found that pain acceptance was associated with lower emotional distress and disability (Lami et al, 2018), and better functional level and less symptoms (Tangen et al, 2020), and that pain-related psychological flexibility and general psychological acceptance were related to functional status (Trainor et al, 2019). Surprisingly, despite this evidence, no study has considered pain acceptance as a variable of interest in the configuration of FM subgroups.…”
mentioning
confidence: 99%
“…Research has repeatedly shown that pain catastrophizing and pain acceptance are important predictors of self-reported physical functioning in samples with acute [ 104 , 105 ] and chronic pain [ 105 , 106 ], including FM [ 41 , 107 , 108 , 109 , 110 ]. Our findings are consistent with the previous evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with fibromyalgia specifically, the previous literature is consistent with the positive role of acceptance in the suffering ( Tangen et al, 2020 ). In this vein, it seems that accepting the disease reduces the levels of anxiety, depression and pain and improves the functioning of these women ( Rodero et al, 2011 ; Yu et al, 2017 ; Lami et al, 2018 ; Trainor et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%